If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2(x + 2) = 3x + -8 + 3(3x + 2) Reorder the terms: -2(2 + x) = 3x + -8 + 3(3x + 2) (2 * -2 + x * -2) = 3x + -8 + 3(3x + 2) (-4 + -2x) = 3x + -8 + 3(3x + 2) Reorder the terms: -4 + -2x = 3x + -8 + 3(2 + 3x) -4 + -2x = 3x + -8 + (2 * 3 + 3x * 3) -4 + -2x = 3x + -8 + (6 + 9x) Reorder the terms: -4 + -2x = -8 + 6 + 3x + 9x Combine like terms: -8 + 6 = -2 -4 + -2x = -2 + 3x + 9x Combine like terms: 3x + 9x = 12x -4 + -2x = -2 + 12x Solving -4 + -2x = -2 + 12x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12x' to each side of the equation. -4 + -2x + -12x = -2 + 12x + -12x Combine like terms: -2x + -12x = -14x -4 + -14x = -2 + 12x + -12x Combine like terms: 12x + -12x = 0 -4 + -14x = -2 + 0 -4 + -14x = -2 Add '4' to each side of the equation. -4 + 4 + -14x = -2 + 4 Combine like terms: -4 + 4 = 0 0 + -14x = -2 + 4 -14x = -2 + 4 Combine like terms: -2 + 4 = 2 -14x = 2 Divide each side by '-14'. x = -0.1428571429 Simplifying x = -0.1428571429
| 9.6=y/3 | | -2(7u-4)+5u=3(u+2) | | a^2-x-20=0 | | -2(6w-5)+6w=8+4(3w-1) | | 20.48=u/8 | | w+(w+3)+w+(w+3)=42 | | 40x=39(x+45) | | (5X-2)+2x=8 | | X/-15=4 | | 5x+4=.25 | | Ix+cI=C | | 0.7(8x+16)=1.6-(x+2) | | (2-X)+5=7 | | 9x/(7x-14) | | 2x-4x+3x-4+5x= | | a^2-22a+185=0 | | 3/2(20)-4 | | Xsquared-6x=6 | | 2w+3=4w+-5 | | 3+2q-(4q+9)-(5q+6)= | | 6(x+3)-3(x+2)=27 | | 57-(5x+4)=5(x+4)+x | | 24=16tsquared | | 26x-8-16x+2=26x-4-16x+17 | | 6(2+4y)=2y+4y+8y | | 3.5(1)=3.5 | | x/0.9=7.2 | | (72y^3)/(64y^7) | | ((x)/(0.01-x)(0.02-x))=0.45 | | 10p+56=176-p | | (72y^3/64y^7) | | b/6=-28 |